THE USE OF ARTIFICIAL INTELLIGENCE IN CONDUCTING INVESTIGATIVE ACTIONS: PROSPECTS, CHALLENGES, AND LEGAL IMPLICATIONS AND THE ROLE OF AI IN PREDICTING CRIMES (World Conference on Social Sciences, Law and Public Policy, 2026)
The rapid development of artificial intelligence (AI) technologies has significantly transformed various sectors, including law enforcement and criminal justice. This article examines the prospects of using AI in conducting investigative actions, focusing on its potential to improve efficiency, accuracy, and objectivity. The study also analyzes legal, ethical, and human rights challenges associated with AI integration into investigative processes. By reviewing international practices and emerging technologies, the paper highlights both opportunities and risks, proposing recommendations for the responsible implementation of AI in investigative activities.
Keywords: Artificial Intelligence, Crime Prediction, Investigation, Criminal Justice, Digital Evidence, Human Rights, Machine Learning, Predictive Policing, Data Analysis, Law Enforcement, Risk Assessment, Big Data, Algorithmic Decision-Making